A year down yonder - Peck, Richard 1934- (New York Puffin Books, 2002)
In 1937, during the Depression, fifteen-year-old Mary Alice, initially apprehensive about leaving Chicago to spend a year with her fearsome, larger-than-life grandmother in rural Illinois, gradually begins to better understand and admire her grandmother's unusual qualities.
Newberry Medal winner, 2001
Sequel to: A long way from Chicago.
Newbery Medal, 2001
Keywords: Grandmothers -- Fiction; Depressions -- 1929 -- Fiction; Country life -- Illinois -- Fiction; Illinois -- Fiction